2018
DOI: 10.1007/s11357-018-0010-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade systemic inflammation is associated with functional disability in elderly people affected by dementia

Abstract: The decline in basic and instrumental activities of daily living (BADLs and IADLs, respectively) is a well-established clinical hallmark of dementia. Growing evidence has shown that systemic subclinical inflammation may be related to functional impairment. We evaluated the possible association between low-grade systemic inflammation and functional disability in older individuals affected by dementia. We explored the association between high-sensitivity C-reactive protein (hs-CRP) levels and BADLs/IADLs in olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Beyond the calf muscle pump dysregulation that acts as a trigger for thrombotic events, chronic inflammation could itself mediate the risk of VTE in older patients through the functional limitation. Several studies have found that elderly patients, particularly women, with high levels of cytokines and inflammation markers such as IL-6 and CRP, had lower muscle strength and higher walking impairment than those with reduced serum levels [ 43 , 44 , 45 , 46 , 47 ].…”
Section: The Complex Molecular Interplay Between the Three Componementioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the calf muscle pump dysregulation that acts as a trigger for thrombotic events, chronic inflammation could itself mediate the risk of VTE in older patients through the functional limitation. Several studies have found that elderly patients, particularly women, with high levels of cytokines and inflammation markers such as IL-6 and CRP, had lower muscle strength and higher walking impairment than those with reduced serum levels [ 43 , 44 , 45 , 46 , 47 ].…”
Section: The Complex Molecular Interplay Between the Three Componementioning
confidence: 99%
“…Finally, subtle neurological signs are particularly prevalent [ 63 ] in older persons and their presence could be interpreted as the presence of multiple neurological disease related to aging, such as PD plus chronic vascular lesions related to hypertension [ 64 ], or normal pressure hydrocephalus associated with vascular lesions. Therefore, these chronic neurological diseases in older persons could change the trajectory of an isolated neurodegenerative disease if they are present simultaneously in older subjects [ 45 ]. Interestingly, postural abnormalities are associated with an increased DVT risk in PD patients.…”
Section: The Comprehensive Geriatric Assessment As a Useful Tool Fmentioning
confidence: 99%
“…Whether lower levels of chronic or acute systemic inflammation may also have similar hippocampal effects is not known. There is supportive evidence that low-grade systemic inflammation does result in worsened functional disability in elderly patients with dementia (Cervellati et al 2018). In addition, neurocognitive impairment associated with the aging process in primates has been associated with neuroinflammatory features seen in the current rat sepsis model, such as microglial activation (Shobin et al 2017).…”
Section: Discussionmentioning
confidence: 95%
“…After all, a vast array of toxic or allergenic substances, in addition to microbes, can threaten body homeostasis and launch the immune response as a protective mechanism, which can inadvertently harm the brain. In fact, given that a number of patients with neurodegenerative diseases present with low-grade systemic inflammation [12][13][14][15][16][17][18], it is not surprising that the altered immune response may affect brains with BBB abnormalities and/or impair neurovascular unit function leading to increased BBB permeability and peripheral cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many patients suffering from neurological disorders present a persistently heightened systemic inflammatory state referred to as low-grade systemic inflammation which is a risk factor for morbidity and mortality in the elderly [ 12 ]. Older patients with dementia, and even old individuals without dementia, experience low-grade systemic inflammation characterized by increased high-sensitivity C-reactive protein (hs-CRP) levels associated with increased cognitive decline [ 13 ]. A study by Miller et al showed an increased prevalence of the non-thyroid autoimmune disease in patients diagnosed as frontotemporal dementia with motor neuron disease and symptomatic C9ORF72 mutation carriers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%